An Unusual Case of Pemphigus Foliaceus Arising in a Patient with Psoriasis Vulgaris - Nurrachmat Mulianto; Osdatilla Esa Putri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Pemphigus foliaceus (PF) is a rare autoimmune blistering disease characterized by superficial, fragile blisters. Psoriasis vulgaris, a chronic inflammatory skin condition, has been rarely associated with PF. This case report presents an unusual instance of PF developing in a patient with a history of psoriasis vulgaris. Case presentation: A 54-year-old Indonesian woman presented with a one-year history of scaly skin and reddish spots across her body, worsening over the past week. She had a prior diagnosis of psoriasis vulgaris and was undergoing methotrexate therapy (15 mg/week) without significant improvement. Three months prior, she developed loose blisters on her back that spread to her hands, rupturing easily and leaving painful sores. The patient denied any mucosal involvement. One week before her presentation, her symptoms worsened following relocation-related stress. Dermatological examination revealed generalized multiple erythematous patches with scales, some with ruptured blisters leaving erosions, and a positive Nikolsky sign. Histopathological examination confirmed PF. The patient was treated with intravenous methylprednisolone, oral erythromycin and paracetamol, topical mupirocin, and clobetasol. After one month, due to a lack of improvement, azathioprine was added, leading to lesion improvement without side effects. Conclusion: This case highlights the rare but potential development of PF in patients with psoriasis vulgaris. The complex interplay between these two conditions warrants further investigation. Early diagnosis and appropriate treatment are crucial for managing PF and improving patient outcomes.